Synthesis and characterization of hybrid organic/inorganic nanotubes of the imogolite type and their behaviour towards methane adsorption - Bottero, Ilaria; Bonelli, Barbara; Ashbrook, Sharon E; Wright, Paul A; Zhou, Wuzong; Tagliabue, Marco; Armandi, Marco; Garrone, Edoardo (Physical chemistry chemical physics : PCCP, 2011)
Imogolite-like nanotubes have been synthesised in which SiCH(3) groups have been introduced in place of the SiOH groups that naturally occur at the inner surface of imogolite, an alumino-silicate with formula (OH)(3)Al(2)O(3)SiOH, forming nanotubes with inner and outer diameter of 1.0 and 2.0 nm, respectively. The new nanotubular material, composition (OH)(3)Al(2)O(3)SiCH(3), has both larger pores and higher specific surface area than unmodified imogolite: it forms as hollow cylinders 3.0 nm wide and several microns long, with a specific surface area of ca. 800 m(2) g(-1) and intriguing surface properties, due to hydrophobic groups inside the nanotubes and hydrophilic Al(OH)Al groups at their outer surface. Adsorption of methane at 30 °C has been studied in the pressure range between 5 and 35 bar on both the new material and unmodified imogolite: it resulted that the new material adsorption capacity is about 2.5 times larger than that of imogolite, in agreement with both its larger pore volume and the presence of a methylated surface. On account of these properties and of its novelty, the studied material has several potential technical applications, e.g. in the fields of gas chromatography and gas separation.